Incorporating Drainage Modeling with Development Plan to Reduce Climate Change Induced Water Logging in Urban Areas of Bangladesh: A Case Study of Khulna City (Journal of Bangladesh Institute of Planners, 2016)
Bangladesh is considered to be one of the most vulnerable countries in the world to climate change due to its vast low laying area. The Khulna City is located in the coastal area of Bangladesh and the main natural hazard affecting the city is water logging, which is associated with rain water stagnation and lack of proper development plan. The objective of the study is to investigate the role of drainage modeling integrating with the development plan to reduce climate change induced water logging in the urban area of Bangladesh. For this study topography condition and watersheds analysis was conducted for the Khulna City. Drainage capacity of waterlogged areas was analyzed comparing drainage density map and inundation map. Drainage model preparation procedure and framework for incorporating with development plan was also developed. Low topography of Khulna City is responsible for severe water logging problem. Areas in ward 19, ward 20, ward 23, ward 24 and ward 27 have higher drainage density but are inundated frequently during heavy rainfall, because of the gaps in the development plan. Drainage modeling may help the development authority for decision making, especially on drainage and water related issues to solve the water logging problems of the study area. Other urban areas of Bangladesh may also apply such models in solving their water logging problems.JBIP, Vol. 9, 2016 (Printed in April 2018), pp. 59-68